Morphological Study of Fasciola Parasites Isolated from Cattle and Sheep in Golestan Province (Iran) - Ahmad Halakou; Hooshang Khazan; Mojgan Bendehpour; Bahram Kazemi (Novelty in Biomedicine, 2017)
Background: The genus Fasciola parasite causes fascioliasis infection. Fascioliasis is widespread all around the world and it is finding in abundance in the northern provinces of Iran. Cattle and sheep are the main hosts of the Fasciola parasite and intermediate hosts are lymnaeid snails such as Galba and Fossaria. Two main species of this genus are F. hepatica and F. gigantica. One of the most important methods of diagnosing this worm is morphological method. The aim of this study is to identify Fasciola through the morphological method in Golestan province. Materials and Methods: Fasciola worms taken from infected livestock livers were washed three times with PBS and were stained with carmine alum. After staining using Valero و and Periago Periago methods, the worms were measured morphologically by و   بcalibrated میکروسکوپ microscope, واستریومیکstereomicroscope, and True Chrome II camera. SPSS version 19 was used for analysis of the data. Results: A total of 45 livers from infected sheep and cattle with Fasciola worms were taken out of 228 samples, including 84 Fasciola hepatica (36.18%), 117 Fasciola gigantica (51.31%) and 27 Fasciola  sp. (11.84%). Conclusion: This مطالعه study نشان showed داد کهthat هر the two main species of worms that isگ شاخصF.hepatica وand F. gigantica were foundژیگانتیکا inبه فراوانیabundance یافتin Golestan province. The current study was unable to identify 11.84% genus Fasciola showed as Fasciola sp.